THE ROLE OF THE COMMUNITY IN DEVELOPING EDUCATION AT THE DONOWANGUN PEKALONGAN ELEMENTARY MADRASAH - Arditya Prayogi; M. Abdul Mufid; M. Ali Ghufron (CV Pena Jaya Pers, 2024)
The community always yearns for a quality educational institution. Because it does not stand alone, educational institutions also need to build relationships with other educational institutions and social organizations. This article aims to determine the role of the community in efforts to develop human resources and in efforts to develop infrastructure at the Salafiyah Donowangun Pekalongan Elementary Madrasah. This article was written with a qualitative approach based on interviews, observations and documentation. From the results of the study, it was obtained that the role of the community in developing human resources at the Elementary Madrasah can grow and develop in conditions of openness and mutual trust between the madrasah and the community. In addition, in the development of facilities and infrastructure, it can be seen from the participation of the community in providing ideas by planning the procurement of facilities and infrastructure needed by the madrasah, and proposing considerations for the management of the madrasah's budget plan.